EFFECT OF MICROBUBBLE OZONATION ON THE EXISTENCE OF TRIHALOMETHANES AND HALOACETIC ACIDS PRECURSORS IN PEAT WATER TREATMENT - Qadafi, Muammar
The need for water is increasing along with the times, but the quality of raw water sources continues to decline. Peat water is a water source that can be used by people living in peat swamp areas. On the other hand, peat water is rich in hydrophobic natural organic matter which is the main precursor to disinfection products (DBPs), compounds formed from the reaction between chlorine disinfectants and natural organic compounds (NOM). Several types of DBPs are carcinogenic, including trihalomethane-4 (THM4) and haloacetic acid-5 (HAA5). Based on literature studies, the ozonation process can reduce the formation of THM4 and HAA5 in water treatment containing high concentration of natural organic matter (NOM). This happens because ozone can change the hydrophobic NOM which is the main precursor of DBPs to a simpler hydrophilic NOM. The Hydrophilic NOM has smaller precursor properties to THM4 and HAA5 when compared to the hydrophobic NOM.